Serological, Biochemical and Radiological Comparison of Triple Hepatitis (Hepatitis B, C & D Virus) and Dual Hepatitis (Hepatitis B & D Virus) at a Hepatology Clinic (Medical Forum Monthly, 2024)
Objectives: To compare the serological, biochemical and radiological parameters of triple hepatitis (Hepatitis B, C & D) and dual hepatitis (Hepatitis B & D) infection.Study Design: Cross Sectional Study.Place and Duration of Study: This 3½ study conducted at Hepatology clinic and wards of Medicine Department, Chandka Medical College (C.M.C), Larkana from January 2008 to June 2011.Materials and Methods: Blood sample of 1713 HBsAg positive patients were drawn, for detection of anti-HDV Antibodies, anti – HCV antibodies on ELISA, HBV DNA, HCV RNA and HDV RNA on PCR and liver function tests (LFT). Ultrasound of all patients was performed. Serological, biochemical and radiological parameters were compare in triple hepatitis and dual hepatitis patients by chi-square test. P value of less than 0.05 was taken as statistically significant.Results: Of 1713 patients, anti-HCVAb was detected in 420 (24.5%) and anti-HDVAb in 1116 (65.1%). 268 (15.6%) had triple hepatitis and 848 (49.5%) had double hepatitis. HDV RNA was detected in 100% patients of TH positive as compared to 74.1% of DH (p < 0.001). TH patients tend to have normal liver span [OR: 11.28 (95% CI: 8.19 – 15.13). TH and DH patients, had features of advanced liver diseases, but no other statistically significant serological, biochemical or radiological difference was noted between both.Conclusion: TH infection was documented in 15.6% and DH in 49.5% HBsAg positive patients. Infected patients had advanced liver disease. There was no statistically significant major difference noted in serological, biochemical or radiological parameters of TH and DH.